18F‐Florzolotau Tau Positron Emission Tomography Imaging in Patients with Multiple System Atrophy–Parkinsonian Subtype. Issue 9 (21st July 2022) - Liu, Feng‐Tao; Li, Xin‐Yi; Lu, Jia‐Ying; Wu, Ping; Li, Ling; Liang, Xiao‐Niu; Ju, Zi‐Zhao; Jiao, Fang‐Yang; Chen, Ming‐Jia; Ge, Jing‐Jie; Sun, Yi‐Min; Wu, Jian‐Jun; et al.
ABSTRACT: Background: Anecdotal evidence suggests that patients diagnosed with the parkinsonian subtype of multiple system atrophy (MSA‐P) may show uptake of the second‐generation tau positron emission tomography (PET) tracer 18 F‐Florzolotau (previously known as 18 F‐APN‐1607) in the putamen. Objectives: This study systematically investigated the localization and magnitude of 18 F‐Florzolotau uptake in a relatively large cohort of patients with MSA‐P. Methods: 18 F‐Florzolotau PET imaging was performed in 31 patients with MSA‐P, 24 patients with Parkinson's disease (PD), and 20 age‐matched healthy controls. 18 F‐Florzolotau signal in the striatum was analyzed by visual inspection and classified as either positive or negative. Regional 18 F‐Florzolotau binding was also expressed as standardized uptake value ratio (SUVR) to assess whether it was associated with core symptoms of MSA‐P after adjustment for potential confounders. Results: By visual inspection and semiquantitative SUVR comparisons, patients with MSA‐P showed elevated 18 F‐Florzolotau uptake in the putamen, globus pallidus, and dentate—a finding that was not observed in PD. This increased signal was significantly associated with the core symptoms of MSA‐P. In addition, patients with MSA‐P with cerebellar ataxia showed an elevated 18 F‐Florzolotau uptake in the cerebellar dentate. Conclusions: 18 F‐Florzolotau tau PET imaging findings may reflect the clinical severity of MSA‐P and can potentially discriminate between this condition and PD. © 2022 International Parkinson and Movement Disorder Society. Abstract : MSA‐P showed elevated 18 F‐Flozolotau uptake in the putamen, globus pallidus, and dentate ‐ a finding that was not observed in PD or healthy control. This increased signal may reflect the clinical severity of MSA‐P and have the potential for discriminating between this condition and PD.